Transforming crustacean waste into an eco‐friendly scale inhibitor: Advancing green water treatment solutions - Khamis, Essam; Abd‐El‐Khalek, Dalia E.; Abdel‐Kawi, Mervat A.; Anwar, Jilan M. (Water and environment journal : WEJ, 2025)
The production and consumption of various shrimp species generate significant amounts of shrimp biowaste. This study explored the potential of shrimp shell waste to prevent scale precipitation, a critical issue in many industries. We assessed the efficacy of shrimp shell extract in inhibiting the formation of different types of scales, including calcium carbonate, strontium carbonate, calcium sulphate and barium sulphate, and compared the results with those of the commonly used commercial antiscalant, HEDP. In addition to microscopic inspection, we conducted conductivity tests, standard NACE tests and electrochemical measurements. The results demonstrate that shrimp shell extract significantly inhibits various scale types, particularly calcium scales compared to commercial antiscalants. This efficiency is attributed to the presence of multiple functional groups which effectively adsorbed on‐scale microcrystals, modifying their structures and inhibiting further growth. Shrimp shell extract offers a cost‐effective, biodegradable and environmentally friendly alternative to conventional non‐green‐scale inhibitors, meeting the growing demand for environmentally friendly phosphorus‐free alternatives.